2019
DOI: 10.1039/c9cc03321a
|View full text |Cite
|
Sign up to set email alerts
|

Redox active [Pd2L4]4+ cages constructed from rotationally flexible 1,1′-disubstituted ferrocene ligands

Abstract: Two new ferrocene-containing [Pd2(LFc)4]4+(X−)4 (where X− = BF4− or SbF6−) self-assembled cages were synthesised from the known, rotationally flexible, 1,1′-bis(3-pyridylethynyl)ferrocene ligand (LFc). The cages were shown to bind neutral and anionic guest molecules and displayed reversible redox activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
46
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 67 publications
9
46
0
3
Order By: Relevance
“…This indicated that there is no electronic communication between the Fc units within C ⋅ BF 4 (Supporting Information). The electrochemical data was consistent with our previous work on the related [Pd 2 ( L 3EFc ) 4 ] 4+ system [15] …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This indicated that there is no electronic communication between the Fc units within C ⋅ BF 4 (Supporting Information). The electrochemical data was consistent with our previous work on the related [Pd 2 ( L 3EFc ) 4 ] 4+ system [15] …”
Section: Resultssupporting
confidence: 92%
“…Two BF 4 − counterions were found to reside in the cavity of the structure. The Pd–N bond lengths ranged from 1.98(2) to 2.07(2) Å, similar to our previously reported [Pd 2 ( L 3EFc ) 4 ] 4+ ferrocene cage [15] and other [Pd n (L) 2n ] n+ systems [17–19] . The thin needles of C ⋅ SbF 6 again gave modest diffraction but the structure was solved in the rhombohedral space group normalR3 and showed the presence of the [Pd 3 ( L 4EFc ) 6 ] 6+ double‐walled triangle molecular architecture (Supporting information).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Among such motifs, metallocenes [35][36][37][38][39][40][41][42][43][44] can display conformational isomerism by rotation of the cyclopentadiene ligands with respect to one another. The different eclipsed and staggered conformations of metallocenes offer a large range of possible dihedral angles between covalently-connected substituents, rendering such building blocks attractive in the synthesis of low-symmetry metal-organic assemblies.…”
Section: Introductionmentioning
confidence: 99%